Hip Stability Isometric Test (HipSIT): Concurrent Validity and Reference Values for CrossFit® Participants - Thiago R T Santos; Ana Luiza R Rodrigues; Henrique M P Faria; Stéphane M Teixeira; Livia S Pogetti; Andressa Silva; Renan A Resende; Juliana M Ocarino (North American Sports Medicine Institute, 2024)
# Background The Hip Stability Isometric Test (HipSIT) is a practical clinical assessment of posterolateral hip muscle performance. There is no information regarding the validity of the HipSIT in participants exposed to high-intensity training, such as CrossFit®. # Purpose The purpose of this study was to investigate the Hip Stability Isometric Test (HipSIT) concurrent validity with the isokinetic assessment in CrossFit® participants. A secondary purpose was to characterize posterolateral hip muscular performance with HipSIT according to sex and lower limb dominance in athletes who participate in CrossFit®. # Study Design Cross-sectional. # Methods One-hundred and eleven CrossFit® participants were evaluated. The posterolateral hip muscles were evaluated using the HipSIT with a hand-held dynamometer. The hip extensors and abductors' peak torque and maximum work were assessed with the Biodex System® 4 Pro isokinetic dynamometer at 60º/s. Concurrent validity between measurements was assessed with the Spearman correlation coefficient and Bland-Altman analyses. The comparison of results between sexes and between limbs was also performed. # Results Spearman analyses indicated a significant positive correlation with medium effect size between HipSIT and isokinetic variables ($ρ$ = 0.36 to 0.49). Bland-Altman analyses showed that most measures were within the 95% limits of agreement. The HipSIT was greater in males than females (p < 0.001) and greater in the dominant than non-dominant limb (p = 0.03). # Conclusion The findings support using HipSIT in the clinical assessment of CrossFit® participants. Clinicians can use the data as reference values for athletes who participate in CrossFit® and should consider the difference between sexes and lower limbs. # Level of evidence 3